Molecular Engineering and Morphology Control of Polythiophene:Nonfullerene Acceptor Blends for High‐Performance Solar Cells. Issue 45 (15th October 2020) - Wang, Qi; Qin, Yunpeng; Li, Miaomiao; Ye, Long; Geng, Yanhou
Abstract: With the advances in organic photovoltaics (OPVs), the development of low‐cost and easily accessible polymer donors is of vital importance for OPV commercialization. Polythiophene (PT) and its derivatives stand out as the most promising members of the photovoltaic material family for commercial applications, owing to their low cost and high scalability of synthesis. In recent years, PTs, paired with nonfullerene acceptors, have progressed rapidly in photovoltaic performance. This Review gives an overview of the strategies in designing PTs for nonfullerene OPVs from the perspective of energy level modulation. A survey of the typical classes of nonfullerene acceptors designed for pairing with the benchmark PT, i.e., poly(3‐hexylthiophene) (P3HT) is also presented. Furthermore, recent achievements in understanding and controlling the film morphology for PT:nonfullerene blends are discussed in depth. In addition to the effects of molecular weight and blend ratio on film morphology, the crucial roles of miscibility between PT and nonfullerene and processing solvent in determining film microstructure and morphology are highlighted, followed by a discussion on thermal annealing and ternary active layers. Finally, the remaining questions and the prospects of the low‐cost PT:nonfullerene systems are outlined. It is hoped that this review can guide the optimization of PT:nonfullerene blends and advance their commercial applications. Abstract : The recent progress in potentially low‐cost polythiophene:nonfullerene‐based solar cells is reviewed from the viewpoints of molecular engineering and morphology control. The molecular design strategies of polythiophenes and nonfullerene acceptors are discussed, followed by the recent achievements in understanding and controlling the morphology of polythiophene:nonfullerene blends. Finally, the future challenges are delineated for advancing the commercial applications of polythiophenes in solar cells.